Mixotrophic protists and a new paradigm for marine ecology: where does plankton research go now?. (15th July 2019) - Flynn, Kevin J; Mitra, Aditee; Anestis, Konstantinos; Anschütz, Anna A; Calbet, Albert; Ferreira, Guilherme Duarte; Gypens, Nathalie; Hansen, Per J; John, Uwe; Martin, Jon Lapeyra; Mansour, Joost S; Maselli, Maira; et al.
Abstract: Many protist plankton are mixotrophs, combining phototrophy and phagotrophy. Their role in freshwater and marine ecology has emerged as a major developing feature of plankton research over recent decades. To better aid discussions, we suggest these organisms are termed "mixoplankton", as "planktonic protist organisms that express, or have potential to express, phototrophy and phagotrophy". The term "phytoplankton" then describes phototrophic organisms incapable of phagotrophy. "Protozooplankton" describes phagotrophic protists that do not engage in acquired phototrophy. The complexity of the changes to the conceptual base of the plankton trophic web caused by inclusion of mixoplanktonic activities are such that we suggest that the restructured description is termed the "mixoplankton paradigm". Implications and opportunities for revision of survey and fieldwork, of laboratory experiments and of simulation modelling are considered. The main challenges are not only with taxonomic and functional identifications, and with measuring rates of potentially competing processes within single cells, but with decades of inertia built around the traditional paradigm that assumes a separation of trophic processes between different organisms. In keeping with the synergistic nature of cooperative photo- and phagotrophy in mixoplankton, a comprehensive multidisciplinary approach will be required to tackle the task ahead.